Systematic review of clinical practice guidelines in kidney transplantation - O'Donoghue, K; Reed, R; Knight, S; O'Callaghan, J; Ayaz-Shah, A; Hassan, S; Morris, P; Pengel, L (Wiley, 2017)
Clinical practice guidelines (CPGs) are widely used to inform the development of protocols for clinical management. Previous work has demonstrated that the quality of CPGs varies widely. This systematic review aimed to determine the quality of CPGs in kidney transplantation in the UK.CPGs in kidney transplantation published between 2010 and 2017 were identified through searches of MEDLINE, NHS NICE Evidence, and websites of relevant UK societies. Using the Appraisal of Guidelines for Research and Evaluation (AGREE) II tool, three appraisers rated the quality of CPGs across six domains, the overall quality of each CPG, and whether it should be recommended for future use. Domain scores were calculated, and inter-rater reliability using the intraclass correlation coefficient (ICC) was reported.Thirteen CPGs met the inclusion criteria. The domain 'clarity of presentation' scored highest, followed closely by 'scope and purpose'. The poorest scoring domains were 'applicability' and 'editorial independence'. Editorial independence also had the widest range of scores. Of the 13 CPGs, one was not recommended for future use, seven were recommended for use with modifications, and five for future use with no need for modification. Mean overall CPG quality was 5 (range 3-6) of a maximum score of 7, and mean inter-rater reliability was substantial with an ICC of 0·71.UK CPGs scored satisfactorily, although with wide variation in how well each domain scored both within and across CPGs. The quality of UK CPGs can still be improved.